PENERAPAN FRAMEWORK COBIT 2019 PADA AUDIT TEKNOLOGI INFORMASI DI PT. LUM - Indra Bakti; Mohamad Firdaus (CV. Denasya Smart Publisher, 2024)
This research aims to evaluate the effectiveness of implementing the COBIT 2019 framework in information technology audits at PT. LUM. COBIT 2019 is a globally recognized framework for the governance and management of enterprise information technology. Using COBIT 2019, this research analyzes the extent to which PT. LUM has implemented effective IT controls and governance to support its business objectives. The research methodology involves qualitative descriptive analysis by collecting data through interviews, questionnaires, and review of internal company documents. The research results show that PT. LUM has implemented most of the processes in the COBIT 2019 domain, but there are still several areas that require further improvement. These findings include the need for improvements in IT risk management, increasing human resource capacity in the IT sector, as well as strengthening monitoring and evaluation mechanisms. From the results of this research, it is recommended that PT. LUM has made improvements to policies and procedures related to IT governance in accordance with the 2019 COBIT recommendations. A more comprehensive implementation of this framework is expected to improve the company's information technology performance, support the achievement of strategic goals, and increase value for stakeholders.